Comparative Study of the Effects of Ferrochelatase‐siRNA Transfection Mediated by Ultrasound Microbubbles and Polyethyleneimine in Combination with Low‐dose ALA to Enhance PpIX Accumulation in Human Endometrial Cancer Xenograft Nude Mice Models. (11th February 2019) - Zhang, Xian; Chen, Longfei; Gao, Lvfen; Gao, Xuesong; Li, Nan; Song, Yuwei; Huang, Xinke; Lin, Shaoqiang; Wang, Xiaoyu
Abstract: Comparison of the fluorescence intensity caused by the accumulation of PpIX in endometrial cancer xenografts in nude mice after low‐dose 5‐Aminolevulinic acid (ALA) injection combined with siRNA transfection was mediated by ultrasound microbubbles and polyethyleneimine (PEI) to explore the feasibility of the ultrasound microbubble technique as transfection agents. Knockdown of ferrochelatase (FECH) in human endometrial cancer xenografts in nude mice was performed by transfection with FECH‐siRNA mediated by PEI and ultrasound microbubbles alone or in combination; then, low‐dose ALA was injected. Subsequently, an in vivo animal imaging system was employed to detect the fluorescence intensity in xenografts. Red fluorescence was observed in xenografts given more than 6.25 mg kg −1 of ALA. When the dose of ALA was greater than 50 mg kg −1, there was a significant difference in the fluorescence between tumor and other tissues. After the nude mice were transfected with siRNA and treated with low‐dose ALA (1.0 mg kg −1 ), apparent PpIX fluorescence of the xenografts was observed, and the fluorescence intensity was PEI+ ultrasound microbubbles > PEI > ultrasound microbubbles. Ultrasound microbubbles in combination with PEI could generate a higher fluorescence intensity of PpIX than that obtained with ultrasound microbubbles or PEI alone, and ultrasound microbubbles could wholly or partially replace PEI under certain conditions. Abstract : Red fluorescence caused by the accumulation of PpIX in endometrial cancer xenografts in nude mice after high‐dose ALA injection could be detected easily by in vivo animal imaging system, but low‐dose ALA (1.0 mg kg −1 ) was injected into xenografts, there was no red fluorescence of tumor. However, knockdown of FECH in nude mice was performed by transfection with FECH‐siRNA mediated by PEI and ultrasound microbubbles alone or in combination, then 1.0 mg kg −1 ALA was injected, apparent red fluorescence of the xenografts was observed, and the fluorescence intensity was PEI+ ultrasound microbubbles > PEI > ultrasound microbubbles.